Top‐down pressure on a coastal ecosystem by harbor seals. Issue 1 (7th January 2019) - Aarts, Geert; Brasseur, Sophie; Poos, Jan Jaap; Schop, Jessica; Kirkwood, Roger; van Kooten, Tobias; Mul, Evert; Reijnders, Peter; Rijnsdorp, Adriaan D.; Tulp, Ingrid
Abstract: Historic hunting has led to severe reductions of many marine mammal species across the globe. After hunting ceased, some populations have recovered to pre‐exploitation levels and may have regained their prominent position as top predator in marine ecosystems. Also, the harbor seal population in the international Wadden Sea grew at an exponential rate following a ban on seal hunting in 1960s, and the current number 38, 000 is close to the historic population size. Here we estimate the impact of the harbor seal predation on the fish community in the Wadden Sea and nearby coastal waters. Fish remains in fecal samples and published estimates on the seal's daily energy requirement were used to estimate prey selection and the magnitude of seal consumption. Estimates on prey abundance were derived from demersal fish surveys, and fish growth was estimated using a Dynamic Energy Budget model. GPS tracking provided information on where seals most likely caught their prey. Harbor seals hauling‐out in the Dutch Wadden Sea fed predominantly on demersal fish, for example, flatfish species (flounder, sole, plaice, dab), but also on sandeel, cod, and whiting. Although harbor seals acquire the majority of prey further offshore in the adjacent North Sea, and only spend 14% of their diving time in the Wadden Sea, seal predation was still estimated to cause an average annual mortality of 43% of the remaining fish in the Wadden Sea and 60% in the nearby shallow coastal waters (<20 m). There were however large sources of uncertainty in the estimated impact of seals on fish, including the migration of fish between the North Sea and Wadden Sea, and catchability estimates of the fish survey sampling gear, particularly for sandeel and other pelagic fish species. Our estimate suggested a considerable top‐down pressure by harbor seals on demersal fish. However, predation by seals may also alleviate density‐dependent competition between the remaining fish, allowing for increased fish growth, and partly compensating for the reduction in fish numbers. This study shows that recovering coastal marine mammal populations could become an important component in the functioning of shallow coastal ecosystems.